2021
DOI: 10.5435/jaaos-d-20-01038
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Burden Contributing to Racial Disparities in Outpatient Versus Inpatient Total Knee Arthroplasty

Abstract: Introduction: Outpatient total knee arthroplasty (TKA) is increasingly common in the setting of early-recovery protocols, value-based care, and removal from the inpatient-only list by the Centers for Medicare & Medicaid Services. Given the established racial disparities that exist in different aspects of total joint arthroplasty, we aimed to investigate whether racial and ethnic disparities exist in outpatient compared with inpatient TKA. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Such results may be potentially due to factors such as language barriers, resource disparity, or geographical issues. While there are no previous studies on the socioeconomic patient characteristic differences between inpatient or outpatient care for pediatric SCHF patients, recent studies on total hip and total knee arthroplasties have emphasized that higher SDI scores are associated with inpatient care, alongside African American race, and existence of comorbidities [ 16 , 24 ]. More specifically, a recent study of adult ambulatory surgical care in New York also reported that Black and Hispanic patients had higher odds of receiving inpatient care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such results may be potentially due to factors such as language barriers, resource disparity, or geographical issues. While there are no previous studies on the socioeconomic patient characteristic differences between inpatient or outpatient care for pediatric SCHF patients, recent studies on total hip and total knee arthroplasties have emphasized that higher SDI scores are associated with inpatient care, alongside African American race, and existence of comorbidities [ 16 , 24 ]. More specifically, a recent study of adult ambulatory surgical care in New York also reported that Black and Hispanic patients had higher odds of receiving inpatient care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given prior research showing non-White patients tend to present for arthroplasty later in disease progression, with more severe arthritis, we were surprised that in our study population Black patients were younger (62.3 vs 68.6) and had lower medical comorbidity (CCI of 2.45 vs 2.92) compared to White non-Hispanic patients. In administrative database and retrospective institutional studies, non-White patients have been found to have higher rates of baseline comorbidity at the time of primary and revision arthroplasty [ 9 , 45 , 48 , 49 ]. It is unclear why comorbidity levels were lower in non-White patients in our study, although this likely reflects a difference in the underlying population captured by the AJRR.…”
Section: Discussionmentioning
confidence: 99%
“…Black patients have more negative hospital metrics as compared with White patients with longer length of stay (LOS) (Amen et al, 2020; Lan & Kamath, 2017; Larrieux, 2017; Singh et al, 2014). There is a greater likelihood that Black patients will be discharged to a skilled nursing facility as compared with home/home health (Amen et al, 2020; Lan & Kamath, 2017; Lasater & Mchugh, 2016; Singh et al, 2014, 2019), which is of concern, as discharge to locations other than home is associated with lower patient satisfaction and poorer clinical outcomes (Wu et al, 2021). Also, 30- and 90-day readmissions are greater for Black patients (Arroyo et al, 2019; Oronce et al, 2015; Wu et al, 2021).…”
Section: Orthopaedic Health Disparitiesmentioning
confidence: 99%
“…Racial disparities associated with arthroplasty have been identified in: (1) rates in use of arthroplasty; (2) hospital metric outcomes; and (3) postoperative outcomes (Amen et al, 2020). The majority of studies examining these disparities have focused on a comparison of Black and White populations, with little data on other minority groups (Mehta et al, 2018;Wu et al, 2021). Unfortunately, much of the literature examining outcomes THA and TKA does not examine race.…”
Section: Orthopaedic Health Disparitiesmentioning
confidence: 99%